Preliminary Investigative Study on the Blood Pressure-Lowering Potential of Aqueous Leaf Extract of Simarouba glauca (AESG) on Normotensive Adult Wistar Rats - Osagie-Eweka, Sammy Davies E.; Orhue, Noghayin E. J.; Amaechina, Fabian C.; Omogbai, Eric K. I.; Moke, Emuesiri Goodies (Biology, Medicine, & Natural Product Chemistry, 2023)
Studies have shown that plants possess medicinal properties and compounds are beneficial in managing and treating diseases, including high blood pressure and related cardiovascular conditions. Simarouba glauca (SG) has been widely reported to possess antibacterial activity, anti-oxidant, anti-proliferative and hemolytic activity; amongst others. However, there is paucity of data on its effect on blood pressure. Hence, the study research aimed at assessing the hypotensive prospect inherent in the aqueous leaf extract of Simarouba glauca (AESG) on normotensive male Wistar rats. The study was conducted using adult male Wistar rats (n = 3), a urethane/thiopental (1205/20 mg/kg) anesthesia and a chart paper attached to Ugo Basile Uni-recorder Model 400700 data capsule. Under full anesthesia, the rat’s trachea and the carotid artery were cannulated for assisted respiration and blood pressure measurement. At stable variables; following the administration of 0.2 mL normal saline, the AESG was administered intravenously via the caudal vein at 2.5 and 5.0 mg/kg body weight dose respectively. The data was recorded on a chart; indicated the characteristic dose-dependent hypotensive effect of AESG on normotensive rats; at doses of 2.5 mg/kg and 5.0 mg/kg, with marked decreases in the systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) from basal levels of 127.83 ± 1.01 mmHg, 91.00 ± 1.00 mm Hg and 103.27 ± 0.99 mm Hg respectively. The outcome of the preliminary investigation indicates that the AESG demonstrated a hypotensive effect on the BP of normotensive male Wistar rats dependent on varying doses administered; indicative of further evaluation.